Peptide-pulsed dendritic cell vaccine in combination with carboplatin and paclitaxel chemotherapy for stage IV melanoma. Issue 4 (August 2017) - Fukuda, Keitaro; Funakoshi, Takeru; Sakurai, Toshiharu; Nakamura, Yoshio; Mori, Mariko; Tanese, Keiji; Tanikawa, Akiko; Taguchi, Junichi; Fujita, Tomonobu; Okamoto, Masato; Amagai, Masayuki; Kawakami, Yutaka
Abstract : In this study, we aimed to evaluate the feasibility and efficacy of peptide-pulsed dendritic cell (DC) vaccine in combination with carboplatin and paclitaxel chemotherapy (DCCP) for patients with stage IV melanoma previously treated with dacarbazine-containing regimen. Six HLA-A24 + and 3 HLA-A02 + patients were treated with carboplatin (area under the curve 5) and paclitaxel (175 mg/m 2 ) on day 1 and DCs (2×10 7 cells) pulsed with Wilms tumor gene 1 (WT1), gp100, tyrosinase, and either MAGE-A3 (for HLA-A24 + ) or MAGE-A2 (for HLA-A02 + ) peptides on days 8 and 22 in 28-day cycle for up to three cycles. DCCP was well tolerated, and median progression-free survival and median overall survival were 2.3 and 12.0 months, respectively. In four of nine patients, a WT1-specific immune response (WT1-IR) was detected using the interferon-γ enzyme-linked ImmunoSpot assay and WT1/HLA tetramer assay. DCCP was more likely to elicit a WT1-IR in patients who received DCs pulsed with the HLA-A24-restricted peptide (75%) compared with patients who received DCs pulsed with the HLA-A02-restricted peptide (0%, P =0.058). Furthermore, three (75%) of four patients with a WT1-IR survived longer than 12 months, whereas only one (20%) of five patients without a WT1-IR who received the BRAF inhibitor after DCCP survived longer than 12 months. These results suggest that DCCP may be beneficial for HLA-A24 + melanoma patients with a WT1-IR.